The Influence of Transformational Leadership on Innovative Work Behavior with Psychological Capital as Mediation and Organizational Citizenship Behavior as Moderation - Aldila Tiarany; Desti Ranihusna (Universitas Negeri Semarang, 2024)
The purpose of this study was to examine the effect of transformational leadership on innovative work behavior through psychological capital as a mediator and organizational citizenship behavior as a moderator in health workers at Rowosari II Health Center and Cepiring Health Center. The population in this study were health workers at both health centers with a sample size of 131 respondents. The sampling technique used saturated sampling. The data collection method used questionnaires and direct interviews, then the data were analyzed and processed using the Structural Equation Modeling (SEM) method based on SmartPLS version 3.0. The results of the indirect analysis showed that psychological capital can fully mediate the effect of transformational leadership on innovative work behavior. The results of the direct analysis showed that transformational leadership has a positive and significant effect on innovative work behavior. Transformational leadership has a significant effect on psychological capital, and organizational citizenship behavior can fully moderate the effect between transformational leadership on innovative work behavior.